Keropok Lekor - Boiling and Steaming Methods of Processing - Bakar, Jamilah (1983)
'Keropok lekor' from Chubb Mackerel (Rastrelliger kanagurta) was precooked by boiling and steaming. They were fried, packed, and then analyzed. Two different formulations were used. They were (i) basic formulation without any preservative and (ii) basic formulation with preservatives added. It was found that the samples tested did not have any significant differences in moisture content, total plate count and thiobarbituric acid value (TBA). However, a significant difference (P<.OI) was observed in the pH changes of samples. Samples which were steamed had significantly lower pH (P<.05). The formulation with preservatives gave the most stable product.